Prof. Mingyon Mun: enthusiasm is the key to success - Lin, Cheng-Ying (Journal of Thoracic Disease, 2017)
On October 28 and 29, 2017, the 16th Annual Meeting of Taiwan Association of Thoracic & Cardiovascular Surgery (TATCS) successfully ended. Established for 31 years, TATCS has developed into an association with a reputation for excellent scientific and educational value. This year, the event took place in Taipei, a city feathered by a glamorous blend of tradition and modernity.